Potential use of soil-born fungi isolated from treated soil in Indonesia to degrade glyphosate herbicide - N Arfarita; T Imai; B Prasetya (Journal of Degraded and Mining Lands Management, 2014)
The glyphosate herbicide is the most common herbicides used in palm-oil plantations and other agricultural in Indonesial. In 2020, Indonesian government to plan the development of oil palm plantations has reached 20 million hectares of which now have reached 6 million hectares.  It means that a huge chemicals particularly glyphosate has been poured into the ground and continues to pollute the soil. However, there is no report regarding biodegradation of glyphosate-contaminated soils using fungal strain especially in Indonesia. This study was to observe the usage of Round Up as selection agent for isolation of soil-born fungi capable to grow on glyphosate as a sole source of phosphorus. Five fungal strains were able to grow consistently in the presence of glyphosate as the sole phosphorus source and identified as Aspergillus sp. strain KRP1, Fusarium sp. strain KRP2, Verticillium sp. strain KRP3, Acremoniumsp. strain GRP1 and Scopulariopsis sp. strain GRP2. This indicates as their capability to utilize and degrade this herbicide. We also used standard medium as control and get seventeen fungal strains. The seventeen fungal strains were identified as species of Botrytis, Fusarium, Aspergillus, Penicillium, Verticillium, Trichoderma and Paecilomyces. These results show the reduction in the number of fungal strains on solid medium containing glyphosate. Of the five isolated fungal species, Verticillium sp. strain KRP3 and Scopulariopsis sp. strain GRP2 were selected for further study based on their highest ratio of growth diameter. This study indicates that treatment of soil with glyphosate degrading fungus would be useful in some areas where this herbicide is extensively used.